How women rise : break the 12 habits holding you back from your next raise, promotion, or job - Helgesen, Sally, 1948-; Goldsmith, Marshall (New York : Hachette Books, 2018)
Ready to take the next step in your career ... but not sure what's holding you back? Read on. Leadership expert Sally Helgesen and bestselling leadership coach Marshall Goldsmith have trained thousands of high achievers--men and women--to reach even greater heights. Again and again, they see that women face specific and different roadblocks from men as they advance in the workplace. In fact, the very habits that helped women early in their careers can hinder them as they move up. Simply put, what got you here won't get you there ... and you might not even realize your blind spots until it's too late. Are you great with the details? To rise, you need to do less and delegate more. Are you a team player? To advance, you need to take credit as easily as you share it. Are you a star networker? Leaders know a network is no good unless you know how to use it. Sally and Marshall identify the 12 habits that hold women back as they seek to advance, showing them why what worked for them in the past might actually be sabotaging their future success. Building on Marshall's classic best seller What Got You Here Won't Get You There, their new book How women rise is essential reading for any woman who is ready to advance to the next level.
Part 1. On being stuck. Where we're coming from -- Where you are -- When women resist change -- Part 2. The habits that keep women from reaching their goals. The twelve habits -- Habit 1: Reluctance to claim your achievements -- Habit 2: Expecting others to spontaneously notice and reward your contributions -- Habit 3: Overvaluing expertise -- Habit 4: Building rather than leveraging relationships -- Habit 5: Failing to enlist allies from day one -- Habit 6: Putting your job before your career -- Habit 7: The perfection trap -- Habit 8: The disease to please -- Habit 9: Minimizing -- Habit 10: Too much -- Habit 11: Ruminating -- Habit 12: Letting your radar distract you -- Part 3. Changing for the better. Start with one thing -- Don't do it alone -- Let go of judgment -- Remember what got you here.
Includes index.
Keywords: Women -- Vocational guidance; Success in business; Self-realization in women; BUSINESS & ECONOMICS / Careers; BUSINESS & ECONOMICS / Motivational; BUSINESS & ECONOMICS / Personal Success; BUSINESS & ECONOMICS / Women in Business; SELF-HELP / Personal Growth / Success; Self-realization in women; Success in business; Women -- Vocational guidance; Nonfiction; Self-help publications; Self-help publications